PERSEPSI GURU TERHADAP PENGGUNAAN CHATGPT SEBAGAI ASISTENSI MENGAJAR GURU DI SMPS PERTIWI SITEBA KOTA PADANG - Deo Zharfan Perry; Abna Hidayati; Nofri Hendri; Rahmi Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine teachers' perceptions of the use of AI, particularly ChatGPT, as a teaching aid by teachers at SMPS Pertiwi Siteba in Padang City. Based on observations at SMPS Pertiwi Siteba Padang City, a phenomenon was found regarding the adoption of AI among teachers, where teachers utilize ChatGPT in various ways, such as preparing lesson plans, as a source of instant information, reviewing teaching materials, and so on. The problem lies in the fact that the use of ChatGPT by teachers is still not restricted due to the absence of a guidebook and specific rules regarding AI among junior high school teachers and their equivalents. This is important because without clear guidelines for teachers on how to use ChatGPT, teachers will use it according to their teaching needs based on their individual perceptions, which will ultimately determine how teachers make decisions and act at school. Therefore, it is necessary to measure descriptively how teachers perceive the use of AI innovation as an assistance in their teaching. This research is descriptive quantitative research using the Likert scale analysis technique with a questionnaire instrument that has 35 statements and 5 alternative answers, namely Strongly Agree (SS), Agree (S), Doubtful – Doubtful (D), Disagree (D), and Strongly Disagree (SD). This study was conducted on 30 respondents who were active teachers at SMPS Pertiwi Siteba, Padang City. The results of the study show that the use of ChatGPT as an assistant is in the “High” category in terms of utilization, and the overall percentage reaches 79.96%, which is in the “Good” category. Thus, teachers' perceptions greatly impact how ChatGPT is used as a teaching assistant.